Vaxxed [videorecording (DVD)] : from cover-up to catastrophe - Blaxill, Mark F.; Blaxill, Michaela (Cinema Libre Studio, 2016)
A documentary alleging that the CDC, the government agency charged with protecting the health of American citizens, destroyed data on their 2004 study that showed a link between the MMR vaccine and autism.